Blood eosinophil count and GOLD stage predict response to maintenance azithromycin treatment in COPD patients with frequent exacerbations. (July 2019) - Djamin, Remco S.; Bafadhel, Mona; Uzun, Sevim; Russell, Richard E.K.; Ermens, Anton A.M.; Kerstens, Rene; Aerts, Joachim G.J.V.; Pavord, Ian D.; van der Eerden, Menno M.
Abstract: Introduction: Maintenance treatment with macrolides are useful in preventing COPD exacerbations. We investigated which characteristics of COPD patients with frequent exacerbations predicted the best response to maintenance treatment with azithromycin. Methods: This study was part of the COLUMBUS trial, a prospective randomized, double-blind, placebo-controlled study in 92 COPD patients with frequent exacerbations. During the 1-year treatment period, follow-up data were collected for spirometry, mMRC scores, sputum cultures and blood inflammatory markers. Results: In the azithromycin group a significant lower number of exacerbations per patient was observed in patients with the following characteristics: baseline blood eosinophil count ≥2.0% (x̄ = 1.26), compared to an eosinophil count < 2.0% (x̄ = 2.50; p = 0.02), GOLD stage 1–2 (x̄ = 1.06), versus GOLD stage 4 (x̄ = 2.62; p = 0.02) and GOLD group C (x̄ = 0.45) compared to group D (x̄ = 2.18; p < 0.01). Moreover, the number of hospitalizations was significantly lower in patients, with a blood eosinophil count ≥2.0% (x̄ = 0.26) compared to an eosinophil count < 2.0% (x̄ = 0.90; p = 0.01) and in GOLD stages 1–2 (x̄ = 1.06) compared to stage 4 (x̄ = 2.62; p = 0.04). Conclusion: In conclusion, azithromycin maintenance treatment appears to be effective in COPD patients with frequent exacerbations, who are either classified in GOLD stage 1–2 or GOLD C and those with a blood eosinophil count of ≥2.0%. Highlights: Blood eosinophil count of ≥2.0% predicts response on azithromycin. GOLD stage 1–2 predicts response on azithromycin. GOLD C predicts response on azithromycin.